Strategi Pengelolaan Dusung di Desa Liang Kecamatan Teluk Elpaputih Kabupaten Maluku Tengah - Evelin Parera; Cornelia M. A Wattimena (Jurnal Sylva Scienteae, 2025)
This study aims to analyze the strategy of Dusung management to increase productivity and sustainability in Liang Village, Teluk Elpaputih District. Dusung is a traditional agroforestry system that has long been applied by the Maluku community. This system has an important role in maintaining food security, improving the economic welfare of the community, and preserving the environment. However, in recent years, Dusung management has faced various challenges, such as changes in land use patterns, minimal technological support and limited market access. The methods used in this study include surveys, in-depth interviews, field observations, and SWOT and AHP analyses to determine priority strategies. The results of the study indicate that the most effective approach in Dusung management is increasing farmer capacity through training, developing Dusung-based ecotourism, and investing in marketing and distribution infrastructure. By implementing this strategy, it is hoped that Dusungs can continue to provide economic, social and environmental benefits to the local community.